Handbook of digital games - Agius, Harry; Angelides, Marios C. (Wiley-IEEE Press, 2014)
"The first book to draw the various traditional and emerging facets of gaming together into a single volume, Handbook of Digital Games explores all the necessary facets to design modern digital game, including MPEG-4, MPEG-7, MPEG-21, Virtual Reality, autonomous Artificial Intelligence, social media function, and multi-generational aspect of modern computer games. Featuring over twenty-five international experts from both academia and game industry, this valuable handbook covers all the basics and current trends of computer games for the engineers in the game industry"-- Provided by publisher